Efektivitas Penggunaan Media Web Genially Berbasis Model E-Learning dengan Tema Zakat dalam Islam - Sufia, Neng; Vebriyanto, Rian (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Abstract Learning media is one of the most important components in the teaching and learning process. Therefore, the researcher intends to develop a web-based learning media using Genially with an e-learning model on the theme